(untitled) (Jurnal Sustainable, 2024)
This study aims to explore the relationship between the implementation of school rules and the level of student discipline. Quantitative research methods use hypothesis testing with Kendall’s Tau analysis and determination correlation analysis to measure the strength and significance of the relationship. The results of the hypothesis test show that the implementation of school rules has a strong and significant correlation with the level of student discipline at SMA Negeri 7 Yogyakarta. Kendall’s Tau analysis score of 0.000, smaller than the significance level of 0.01, confirms that the relationship between school rule implementation and student discipline is significant. A closeness of 0.568 indicates that the relationship is not only significant, but also strong and positive. Regression analysis showed a correlation value (R) of 0.805, indicating a positive relationship between the implementation of school rules and student discipline. The coefficient of determination (R Square) of 0.648 indicates that 64.8% of the variation in student discipline can be explained by the implementation of school rules. Thus, it can be concluded that the better the implementation of school rules, the higher the level of student discipline at SMA Negeri 7 Yogyakarta. The school needs to continue to pay attention and improve the quality of the implementation of school rules to maintain and improve the level of student discipline. In addition, this research contributes in the context of fostering students character and morals.